Communication and change : the last ten years - and the next - "Schramm, Wilbur (ed.)"; Lerner, Daniel (Honolulu, 1976)
This is an excellent of socioeconomic problems in the several Asian countries. Its conclusions could have an impact on the utilization of communications technologies, booth within nations and internationally. An excellent reference for international scholars in several disciplines.
Keywords: Social Psychology .